(untitled) (International Journal of Engineering and Computer Science, 2014)
Many images are degraded by the bad weather conditions due to smoke, fogs, dust and ash which are obstacle in clarity of images. Image processing techniques improve the quality of an image and enhance the maximum information from the degraded image. It is the process of combining two or more images into a single image; method is a fusion-based strategy that derives from two original hazy images inputs by applying a white balance and contrast enhancing procedure.The method performs in a pyramidal method, which is straightforward to implement. Then the resulting image will be more clear and enhanced from the prior. This thesis reports a detailed study performed over a set of image fusion algorithms regarding their implementation. The thesis demonstrates the utility and effectiveness of a fusion-based technique for dehazing based on a single degraded image.